2021
DOI: 10.1111/plb.13332
|View full text |Cite
|
Sign up to set email alerts
|

The seeds of invasion: enhanced germination in invasive European populations of black locust (Robinia pseudoacacia L.) compared to native American populations

Abstract: Local adaptation and the evolution of phenotypic plasticity may facilitate biological invasions. Both processes can enhance germination and seedling recruitment, which are crucial life-history traits for plants. The rate, timing and speed of germination have recently been documented as playing a major role during the invasion process. Black locust (Robinia pseudoacacia L.) is a North American tree, which has spread widely throughout Europe. A recent study demonstrated that a few populations are the source of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…Black locust exhibits a high genetic diversity in its native range (Mebrahtu & Hanover, 1989; Surles et al, 1989) as well as in China (Guo et al, 2022), but studies directly comparing the genetic composition between native and non‐native populations are still lacking. Bouteiller et al (2021) found differences in the phenotypic plasticity between native and non‐native (European) populations of black locust, with an increased germination rate in the European populations. Furthermore, numerous other studies investigated black locust in its non‐native range and found a generally high degree of phenotypic plasticity, also in comparison with other trees (e.g., Granata et al, 2020; Guo et al, 2018; Luo et al, 2016; Mantovani et al, 2014; Su et al, 2021; Xu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Black locust exhibits a high genetic diversity in its native range (Mebrahtu & Hanover, 1989; Surles et al, 1989) as well as in China (Guo et al, 2022), but studies directly comparing the genetic composition between native and non‐native populations are still lacking. Bouteiller et al (2021) found differences in the phenotypic plasticity between native and non‐native (European) populations of black locust, with an increased germination rate in the European populations. Furthermore, numerous other studies investigated black locust in its non‐native range and found a generally high degree of phenotypic plasticity, also in comparison with other trees (e.g., Granata et al, 2020; Guo et al, 2018; Luo et al, 2016; Mantovani et al, 2014; Su et al, 2021; Xu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In forestry practice, it may also be sufficient to use a chemical method by immersing the seeds for 60 min in concentrated sulfuric acid, then washing the seeds in cold water and leaving them to dry at adjusted temperature [46]. Another successful method is by scarifying the seeds using manual abrasion sandpaper so that the seed coat is scratched [15,17,47].…”
Section: Discussionmentioning
confidence: 99%
“…Four treatments were applied. The first treatment referred to the mechanical scarification method, using abrasive sandpaper until the tegument was visibly damaged [17]. The second type of treatment (thermal treatment) involved water-soaked seeds at different temperatures [3,6]; seeds were soaked for 10 min in water at a temperature of 100 • C, 70 • C, and 40 • C. For the third treatment, seeds were soaked in biostimulator solution (Foliplant, 0.9%) for 10 min [21].…”
Section: Germination Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Guidobono (pers comm) about 13% and 9.45% of G. triacanthos seeds collected from cow dungs and pots, respectively, germinated in laboratory conditions, while Marcora et al (2018) reported about 15% of seedling emergence, and Ferreras et al (2015) 20.2%. For R. pseudoacacia, Yuan et al (Yuan et al, 2013) reported an emergence rate of 29%, while Bouteiller et al (2021) reported higher values, 60% and 80% in its native range and in Europe, respectively. Each plot was divided into halves by a plastic mesh and was separately sowed by hand with 200 seeds of G. triacanthos (100 seed mass: approximately 17 g) on one side and 200 seeds of R. pseudoacacia (100 seed mass: approximately 2 g) on the other side.…”
Section: Seed Addition and Assessment Of Seedling Recruitmentmentioning
confidence: 99%